Cinematography. 65 mm and 70 mm film. Image areas. Specification for positions and dimensions of image area produced by 65 mm and 70 mm motion-picture camera aperture and maximum projectable image area on 70 mm motion-picture prints Part 4.2.1, (31st December 1980) - British Standards Institution
No abstract available